Lady Jane Wilde's Letters to Mr. John Hilson, 1847-1876 : a Critical Edition. - Tipper, Karen Sasha Anthony (Edwin Mellen Press, 2010)
This work presents the letters of Lady Jane Wilde whose affinity for letter-writing, over a period of thirty years, is captured in her correspondence with a Scot, Mr. John Hilson, whom she only met once during a visit to the Borders. This book contains five color photographs.